Phytochemical Contents, Biological Activities and Therapeutic Applications of Hedera Helix (Ivy Leaf) Extracts: A Review - Shokry, Aya; El-Shiekh, Riham; Kamel, Gehan; Ramadan, Amer (Natural Products Journal, The, 2022)
Background: Herbs have long been used as natural therapeutics, and recent controlled clinical studies have confirmed some of the presumed benefits. Hedera helix(ivy leaves) is a valuable common form related to the family Araliaceae. Many herbal preparations include extracts from their leaves as the principle active ingredient. Objective: The objective of this article is to summarize the pharmacological activities and phytochemical screening of H. helix. Methods: To prepare this article, the data was collected from different sources, including books, thesis, research and etc. Results: The all-published studies depend on isolation, identification, and characterization of different active constituents of H. helix leaves, followed by the determination of biological activities in vivo and in vivo. Chemical screening has shown that H. helix leaves are a rich source of phytochemicals demonstrating therapeutic activities, such as sterols, tannins, terpenoids, glycosides, phenols, emetine alkaloids, flavonoids, saponins, volatile and fixed oils, vitamins, carbohydrates, reducing sugars, and minerals. Further, studies of disease models and clinical trials have demonstrated anti- inflammatory, analgesic, cough suppressant, expectorant, anticancer, antimicrobial, anticoagulant, and smooth muscle relaxant activities. Conclusion: This review summarizes the bioactive constituents of H. helix leaves and their underlying pharmacological mechanisms, clinical efficacies, and safety profiles. We also suggest potential therapeutic uses for COVID-19.
Keywords: chemical constituents